Jihadism transformed: Al-Qaeda and Islamic state’s global battle of ideas. Edited by Simon Staffell and Akil Awan, United Kingdom: C. Hurst & Co. 2016, Pp. 273, ISBN: 978-1-84904-647-3 - Moten, Abdul Rashid (Bangladesh Institute of Islamic Thought, 2017)
Jihadism Transformed, edited by Simon Staffell, a diplomat, and an expert on extremist ideologies, and Akil Awan, an Associate Professor at the University of London, is a collection of essays by a group of eleven scholars who analyze the global competition between Al-Qaedah and the Islamic State in some areas of the world. This book is the product of a gathering of experts convened by the British Foreign and Commonwealth Office on 12 December 2014 to assess how jihadist narratives had evolved in recent years, in the context of turbulent events in the Middle East.....